Stress factors and anger in the risks of road accidents of workers of a healthy company (Dimensión Empresarial, 2025)
Deaths and injuries in traffic accidents are a growing global public health problem, with nearly 1.25 million people dying each year (WHO, 2015). This article seeks to determine the stress,anger, and driving styles of the drivers of a home health care and patient transfer services company in Barranquilla. A descriptive study was undertaken with a population of 100 drivers.80% of these present reactions due to exposure to negative conditions such as traffic congestion, delays in timely service hours, anxiety, stress, exhaustion, high workload, anger oranger. Proving that this work exercise can be very high risk.
Keywords: Anger; Stress; Mental Health; Workers; DECS